Connecting computer science and sport: the RoboCup simulation league - Dauscher, P.; Flentge, F.; Uthmann, T. (International Journal of Computer Science in Sport, 2004)
RoboCup is a most challenging project in the field of Artificial Intelligence and Multi-Agent Technology research. In this article, we will discuss some examples showing that RoboCup Simulation League scenarios can also be interesting in the interdisciplinary cooperation between computer science and sport science. One part of the paper concentrates on the generation of surrogate data which can be used in order to test data analysis methods. Furthermore, we will discuss RoboCup scenarios as testbed for sport theory as a future perspective.